2005
DOI: 10.15381/rpb.v12i2.2404
|View full text |Cite
|
Sign up to set email alerts
|

Diversidad de la familia Orchidaceae en los bosques montanos de San Ignacio (Cajamarca, Perú)

Abstract: La insuficiente información sobre la flora, específicamente sobre la familia Orchidaceae y la inminente desaparición de los bosques en la Vertiente Oriental del río Chinchipe (San Ignacio, Cajamarca), fueron las razones suficientes que motivaron a realizar la presente investigación. La evaluación se realizó en cuatro localidades de la provincia San Ignacio (Cajamarca), durante el año 2000, con 27 cuadrantes de 500 m², distribuidos cada 100 m de altitud, desde los 800 hasta los 2700 m, el método de muestreo fue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
4
0
3
Order By: Relevance
“…Epidendroideae is the dominant subfamily within Orchidaceae, containing around 80 % of the orchid species known (Cribb et al 2003, Hágsater et al 2005. Therefore, it is not surprising that it was also the dominant subfamily at the locality of study (49 species, 66 %); such as it has been recorded in numerous studies (Noguera-Savelli et al 2015, Nurfadilah 2015, Rewicz et al 2015, Zhang et al 2015, Batke et al 2016, Solano-Gómez et al 2016, Castillo-Hernández & Flores-Olvera 2017, González-Aguilar & Burelo-Ramos 2017, Meave et al 2017, Tejeda-Sartorius & Téllez-Velasco 2017, including some conducted within the state of Oaxaca (Soto-Arenas & Salazar 2004, Hágsater et al 2005, and at localities with temperate forests (Cerros-Tlatilpa & Espejo-Serna 1998, Luna-Rosales et al 2007, Huang et al 2008, Calatayud 2005, Rewicz et al 2015, Santiago 2018. Likewise, our results showed that at the locality of study, terrestrial orchids had the greatest species richness (32 species), followed by epiphytes (24 species).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Epidendroideae is the dominant subfamily within Orchidaceae, containing around 80 % of the orchid species known (Cribb et al 2003, Hágsater et al 2005. Therefore, it is not surprising that it was also the dominant subfamily at the locality of study (49 species, 66 %); such as it has been recorded in numerous studies (Noguera-Savelli et al 2015, Nurfadilah 2015, Rewicz et al 2015, Zhang et al 2015, Batke et al 2016, Solano-Gómez et al 2016, Castillo-Hernández & Flores-Olvera 2017, González-Aguilar & Burelo-Ramos 2017, Meave et al 2017, Tejeda-Sartorius & Téllez-Velasco 2017, including some conducted within the state of Oaxaca (Soto-Arenas & Salazar 2004, Hágsater et al 2005, and at localities with temperate forests (Cerros-Tlatilpa & Espejo-Serna 1998, Luna-Rosales et al 2007, Huang et al 2008, Calatayud 2005, Rewicz et al 2015, Santiago 2018. Likewise, our results showed that at the locality of study, terrestrial orchids had the greatest species richness (32 species), followed by epiphytes (24 species).…”
Section: Discussionmentioning
confidence: 71%
“…Similar results were documented by Santiago (2018). However, Calatayud (2005) recorded a strong dominance of epiphytes in a temperate forest dominated by species of Podocarpus. The slightly higher species richness of terrestrial compared with epiphyte orchids found in the present study, might be explained by the dominance of Pinus at the locality of study (UMAFOR 2007), since terrestrial orchids tend to be more numerous in forests dominated by conifers from that genus (Hágsater et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estos bosques montanos de neblina en el Perú se extienden a lo largo del eje noreste y sur oeste, así en el departamento de Cajamarca se encuentran principalmente en las provincias de Jaén y Cajamarca (MINAM, 2014). La provincia de San Ignacio en Cajamarca alberga en su territorio ISSN: 2709-4502 importante área de bosques de neblina los cuales viene siendo menguados a lo largo del tiempo (Calatayud, 2005), parte de estos se ubican en la parte alta de la microcuenca Quanda, que es la fuente hídrica para la hidroeléctica de Quanda en la provincia de San Ignacio (Caritas, 2011).…”
Section: Introductionunclassified
“…Esto ha llevado a muchas firmas comerciales a usar el sistema in vitro por la rapidez de su propagación masiva (Teixeira 2003). Estas técnicas han mostrado resultados poco exitosos en nuestro país, limitándose a la extracción y comercialización directa en el campo, lo cual reduce significativamente el número de éstas en su hábitat, por lo tanto es necesario establecer pautas muy claras y precisas acerca de su conservación o manejo sostenible, puesto que constituyen uno de nuestros patrimonios nacionales (Morel 1974, Teng et al 1997, Torres & Mogollón 2000, Decrose et al 2003, Calatayud 2004, Puchooa 2004, Las auxinas participan en muchos procesos del desarrollo vegetal: crecimiento, dominancia apical, enraizamiento, partenocarpia, tropismos, abscisión, elongación celular y frecuentemente en embriogénesis y organogénesis en cultivos en suspención. Uno de los reguladores más utilizados en la formación de raíces es el ácido indolbutírico (IBA) debido a que no causa efectos fitotóxicos, ni inhibe el crecimiento caulinar (Pierik 1990, Salisbury & Ross 2000.…”
Section: Introductionunclassified